Phonology and phonetics of Singapore Hakka - Chia, Ai Ying (2018)
Hakka is a major branch of the Sinitic language family. The language consists of many varieties due to language contact as, historically, Hakka people migrated southwards within China, and then to other parts of the world, with Singapore being one of the destinations. This results in mutually unintelligible Hakka varieties, such as Taiwanese Hakka and Guangzhou Hakka. Several studies have been conducted on different Hakka varieties, including Hakka in Southeast Asia, but there is a particular lack of research focusing on Singapore Hakka. Hence, this paper aims to set the foundation of a phonological and phonetic study on Singapore Hakka by examining three Hakka varieties spoken in Singapore (Meixian, Wuhua and Jiaoling Hakka).